2001
DOI: 10.1002/1521-4141(200104)31:4<1098::aid-immu1098>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear receptor PPAR gamma is expressed by mouse T lymphocytes and PPAR gamma agonists induce apoptosis

Abstract: Peroxisome proliferator‐activated receptor (PPAR)‐γ is a nuclear hormone receptor that serves as a trans factor to regulate lipid metabolism. Intense interest is focused on PPAR‐γ and its ligands owing to its putative role in adipocyte differentiation. Little is known, however, about the functions of PPAR‐γ in the immune system, especially in T lymphocytes. We demonstrate that both naive and activated ovalbumin‐specific T cells from DO11.10‐transgenic mice express PPAR‐γ mRNA and protein. In order to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
133
3
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(147 citation statements)
references
References 32 publications
7
133
3
4
Order By: Relevance
“…PPAR-␥ protein expression increases as T cells transit from resting to activated state. Initial studies demonstrated that PPAR-␥ activation by synthetic ligands induces lymphocyte apoptosis (25). However, apoptosis occurred at high doses of synthetic agonist, which are generally recognized to be cytotoxic and exert PPAR-␥-independent effects in immune cells (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPAR-␥ protein expression increases as T cells transit from resting to activated state. Initial studies demonstrated that PPAR-␥ activation by synthetic ligands induces lymphocyte apoptosis (25). However, apoptosis occurred at high doses of synthetic agonist, which are generally recognized to be cytotoxic and exert PPAR-␥-independent effects in immune cells (47).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro treatment of splenocytes or fractionated CD4 ϩ T cells with 15-deoxy-PGJ2 and TZD significantly reduces Ag and mitogen-induced proliferation (24,25). PPAR-␥ activation also regulates cytokine secretion by CD4 ϩ T cells (26).…”
mentioning
confidence: 99%
“…One study demonstrated that treatment with high doses of TZDs enhanced T-cell apoptosis (Harris and Phipps, 2001). However, PPARγ activation also resulted in increased survival under conditions of cytokine withdrawal or serum starvation (Jo et al, 2006;Wang et al, 2002).…”
Section: Ppars In T Cells and Autoimmunitymentioning
confidence: 99%
“…Elimination of autoreactive T cells by apoptosis protects CNS tissue from immune-mediated destruction and likely contributes to the resolution of disease (reviewed in [39]). Interestingly, PPAR-γ ligands have been demonstrated to be capable of inducing T-cell apoptosis [19,20], suggesting that these agonists may facilitate the resolution of T-cell-mediated autoimmune diseases. The role of B cells in modulating MS is becoming more appreciated.…”
Section: Ppar-γ: Effects On Peripheral Leukocytesmentioning
confidence: 99%